2012
DOI: 10.1016/j.ejvs.2012.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statin Therapy on Abdominal Aortic Aneurysm Growth: A Meta-analysis and Meta-regression of Observational Comparative Studies

Abstract: Statin therapy is likely effective in prevention of the growth of small AAAs, and may be more beneficial as the baseline diameter increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 30 publications
1
50
0
2
Order By: Relevance
“…418 Based on a recent meta-analysis, statin therapy is likely effective in the prevention of growth of small (,55 mm in diameter) abdominal aortic aneurysms. 419 …”
Section: Iia B 402mentioning
confidence: 99%
“…418 Based on a recent meta-analysis, statin therapy is likely effective in the prevention of growth of small (,55 mm in diameter) abdominal aortic aneurysms. 419 …”
Section: Iia B 402mentioning
confidence: 99%
“…The latter resulted in better survival free from complications such as dissection, rupture or need for repair for those patients receiving statin therapy. To date, no other study investigated the effect of statins on the dilatation of ascending aorta aneurysms, but only on the abdominal aorta [7,8], and on the whole thoracic aorta including aortic arch and thoracic descending aorta [9]. Furthermore, that retrospective study [9] was not adjusted for selection bias.…”
Section: Discussionmentioning
confidence: 95%
“…Etiology is multifaceted, involving systemic hypertension, connective tissue disorders, proinflammatory mediators such as macrophages, T-cells, B-cells and neutrophils, as well as multiple pro-inflammatory transcription factors [6]. Previous studies have shown that statin therapy is likely effective in prevention of the growth of small abdominal aorta aneurysms [7,8]. To date, only one study investigated the effect of statin therapy on thoracic aorta aneurysm growth [9], and found a significant correlation between statin therapy and a decreased progression to dissection, rupture, or death; although no significant difference was found with regard to the aortic root, and the investigation included the whole thoracic aorta.…”
Section: Introductionmentioning
confidence: 98%
“…The beneficial effect of statins through their pleiotropic anti-inflammatory effect is somewhat controversial even today [52]- [54] and, therefore, a high quality randomized control study should be done given the social loss due to this disease, same as a case in IAs. Under these circumstances, recent metaanalysis on the effect of statins on the enlargement of aortic aneurysm reported the beneficial trend of statin usage to prevent the enlargement [55]. Based on these findings together with those from IA researches, statins may be a good candidate of drugs for aneurysm treatments.…”
Section: Effect Of Statins On Ias In Human Casesmentioning
confidence: 88%